Relationship Between Innovation and Exports in Enterprises: A Support Tool for Synergistic Improvement Plans - Alfaro-Marchant, M; Galvez-Manriquez, D (Elsevier Inc., 2022)
Innovation and exports are strong drivers of enterprise competitiveness, therefore the development of models for managing these capabilities has been widely studied. As a result, different approaches have been proposed to explore the synergistic relationship between innovation and exports. The main accepted paradigm is causal; however, recent studies lean towards a common-space approach between the two capabilities. In this research, the objective is to establish improvement plans that exploit the synergistic effects between innovation and export activities in companies. For this, the assessment models of innovation capability and export capability in the literature are studied. These models are the basis for establishing relationships between innovation and export practices or activities based on their similarities and resource use. Then, a model is proposed to establish improvement strategies of innovation capability based on the similarities with export capability and vice versa. This model is applied to a case of study in a company in the wine sector. It is expected that the proposed model will provide a tool for enterprises to simultaneously strengthen innovation and export capabilities. © 2022